Impact of surface structure and feed gas composition on Bacillus subtilis endospore inactivation during direct plasma treatment - Hertwig, Christian; Steins, Veronika; Reineke, Kai; Rademacher, Antje; Klocke, Michael; Rauh, Cornelia; Schlüter, Oliver (Frontiers in Microbiology, 2015)
This study investigated the inactivation efficiency of cold atmospheric pressure plasma treatment on Bacillus subtilis endospores dependent on the used feed gas composition and on the surface, the endospores were attached on. Glass petri-dishes, glass beads and peppercorns were inoculated with the same endospore density and treated with a radio frequency plasma jet. Generated reactive species were detected using optical emission spectroscopy. A quantitative polymerase chain reaction (qPCR) based ratio detection system was established to monitor the DNA damage during the plasma treatment. Argon + 0.135 % vol. oxygen + 0.2 % vol. nitrogen as feed gas emitted the highest amounts of UV-C photons and considerable amount of reactive oxygen and nitrogen species. Plasma generated with argon + 0.135 % vol. oxygen was characterized by the highest emission of reactive oxygen species, whereas the UV-C emission was negligible. The use of pure argon showed a negligible emission of UV photons and atomic oxygen, however the emission of vacuum (V)UV photons was assumed. Similar maximum inactivation results were achieved for the three feed gas compositions. The surface structure had a significant impact on the inactivation efficiency of the plasma treatment. The maximum inactivation achieved was between 2.4 and 2.8 log10 on glass petri-dishes and 3.9 to 4.6 log10 on glass beads. The treatment of peppercorns resulted in an inactivation lower than 1.0 log10. qPCR results showed a significant DNA damage for all gas compositions. Pure argon showed the highest results for the DNA damage ratio values, followed by argon + 0.135 % vol. oxygen + 0.2 % vol. nitrogen. In case of argon + 0.135 % vol. oxygen the inactivation seems to be dominated by the action of reactive oxygen species. These findings indicate the significant role of VUV and UV photons in the inactivation process of Bacillus subtilis endospores.